The role of wheezing subtypes in the development of early childhood asthma - Donald E. Warden; Hongmei Zhang; Yu Jiang; Hasan S. Arshad; Wilfried Karmaus (Respiratory Research, 2025)
Abstract Background Early childhood wheezing is associated with asthma risk at later ages, emphasizing the need for understanding wheezing patterns and their implications for asthma development. Methods Children in the F2-generation (n = 603) of the Isle of Wight Birth Cohort (IOWBC) were followed-up at 3, 6, 12, 24, 36, and 72 months. Prevalence of wheeze and wheeze type (general, infectious, and non-infectious) were recorded. Group-based trajectory models covering ages 3 to 36 months were used to identify early childhood wheezing trajectories for each type of wheeze. These trajectories were examined for their association with asthma status and lung function at 6 years and later. Results Distinct trajectories for general (“Persistent”, “Transient”, “Progressive”, and “Infrequent/Never”), infectious (“Persistent”, “Transient”, and “Infrequent/Never”), and non-infectious (“Progressive”, “Early Occurrence”, and “Infrequent/Never”) wheezing were identified. Compared to the “Infrequent/Never” trajectories, four trajectories were associated with an increased risk of asthma, namely “Progressive” non-infectious, “Early Occurrence” non-infectious, “Persistent” infectious, and “Persistent” general wheeze trajectories. Conclusions The identification of wheeze trajectories across different etiologies as significant risk factors for asthma may aid in understanding the complex, multifactorial nature of asthma onset. The findings suggest that early identification of specific wheeze patterns, not just occurrence of wheezing, can inform clinical interventions and potentially mitigate the risk of developing asthma.